Kontribusi Abdul Karim Soroush dalam Mendialogkan Agama dan Sains - Ainurrofiq, Faiq; Amir, Abdul Muiz; Faruk, Ahmad (FIKRAH, 2022)
This paper explores Abdul Karim Soroush's contribution to the dialogue between religious and scientific knowledge and its consequences for the humanist-anthropocentric development of religious knowledge. Documentation procedures were used to collect the data, which were subsequently examined using content analysis techniques. After doing an analysis, the author draws three conclusions: Soroush first equated religious knowledge and non-religious knowledge. The two are interdependent and will continue to evolve. Therefore, Soroush encouraged conversation so that religious understanding is constantly contextual. Soroush's second argument for the interaction between religious knowledge and science was based on the principle of shrinkage and development. The doctrine of contraction and expansion was inspired by Surah al-Baqarah 245 and the Sufi tradition. Thirdly, Soroush thought religious knowledge would undergo evolution and refinement while conversing with non-religious information. It is anticipated that refining humanist-anthropocentric religious knowledge would bring practical solutions to the human problems from which this religion derives.